'The Other Hospital Staff': Tracing the History of an Eastern Cape Mission Hospital's General Workers, Late 1930s to the Early 1970s - Noble, Vanessa (South African Historical Journal, 2024)
The historical narrative of the Roman Catholic-established Glen Grey Mission Hospital, located in what was the 'Native Reserve' of Ciskei (later forming part of the Transkei 'Bantustan') of today's Eastern Cape province of South Africa, has usually focused on the efforts and activities of its skilled 'European' missionary contributors, particularly its doctors and nurses. Written from a social history perspective, this article extends the historiography of medical missions to trace the fragmentary history of this institution's general workers, such as domestic workers, clerical staff, and general labourers employed to undertake construction, maintenance, transport, stable, and farming work. These workers, by the late-1940s apartheid era, primarily isiXhosa-speaking black Africans, helped build and maintain this institution. This article focuses in particular on the lives and work of three specific drivers who became important assistants to the hospital's doctors. Much of the usually spotlighted, life-saving work done by this hospital's doctors and nurses would not have been possible without the significant supportive and servicing work provided by these workers, most of whom were either marginalised in or erased from this institution's records.